Genetic characterization of perna viridis L. in peninsular Malaysia using microsatellite markers. - Ong, C.C.; Yusoff, Khatijah; Yap, Chee Kong; Tan, Soon Guan (Indian Academy of Sciences, 2009)
A total of 19 polymorphic microsatellite loci were used to analyse levels of genetic variation for 10 populations of Perna viridis L. collected from all over peninsular Malaysia. The populations involved in this study included Pulau Aman in Penang, Tanjung Rhu in Kedah, Bagan Tiang in Perak, Pulau Ketam in Selangor, Muar, Parit Jawa, Pantai Lido and Kampung Pasir Puteh in Johore, and Kuala Pontian and Nenasi in Pahang state. The number of alleles per locus ranged from two to seven, with an average of 3.1. Heterozygote deficiencies were observed across all the 10 populations. Characterization of the populations revealed that local populations of P. viridis in peninsular Malaysia were genetically similar enough to be used as a biomonitoring agent for heavy metal contamination in the Straits of Malacca. Cluster analysis grouped the P. viridis populations according to their geographical distributions with the exception of Parit Jawa. The analysis also revealed that P. viridis from the northern parts of peninsular Malaysia were found to be the most distant populations among the populations of mussels investigated and P. viridis from the eastern part of peninsular Malaysia were closer to the central and southern populations than to the northern populations.